Discover the answers to your questions at Westonci.ca, where experts share their knowledge and insights with you. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
To evaluate the piecewise function [tex]\( f(x) \)[/tex] at the given values of the independent variable, we need to follow the definition of the function for each specific range.
The piecewise function is defined as:
[tex]\[ f(x) = \begin{cases} 3x + 4 & \text{if } x < 0 \\ x + 7 & \text{if } x \geq 0 \end{cases} \][/tex]
Let's evaluate the function at each given value:
### (a) [tex]\( f(-2) \)[/tex]
For [tex]\( x = -2 \)[/tex]:
- Since [tex]\( -2 < 0 \)[/tex], we use the first piece of the function: [tex]\( f(x) = 3x + 4 \)[/tex].
- Substituting [tex]\( x = -2 \)[/tex] into this piece:
[tex]\[ f(-2) = 3(-2) + 4 = -6 + 4 = -2 \][/tex]
Thus, [tex]\( f(-2) = -2 \)[/tex].
### (b) [tex]\( f(0) \)[/tex]
For [tex]\( x = 0 \)[/tex]:
- Since [tex]\( 0 \geq 0 \)[/tex], we use the second piece of the function: [tex]\( f(x) = x + 7 \)[/tex].
- Substituting [tex]\( x = 0 \)[/tex] into this piece:
[tex]\[ f(0) = 0 + 7 = 7 \][/tex]
Thus, [tex]\( f(0) = 7 \)[/tex].
### (c) [tex]\( f(4) \)[/tex]
For [tex]\( x = 4 \)[/tex]:
- Since [tex]\( 4 \geq 0 \)[/tex], we use the second piece of the function: [tex]\( f(x) = x + 7 \)[/tex].
- Substituting [tex]\( x = 4 \)[/tex] into this piece:
[tex]\[ f(4) = 4 + 7 = 11 \][/tex]
Thus, [tex]\( f(4) = 11 \)[/tex].
To summarize:
- (a) [tex]\( f(-2) = -2 \)[/tex]
- (b) [tex]\( f(0) = 7 \)[/tex]
- (c) [tex]\( f(4) = 11 \)[/tex]
Therefore, the values of the function at the given points are:
- [tex]\( f(-2) = -2 \)[/tex]
- [tex]\( f(0) = 7 \)[/tex]
- [tex]\( f(4) = 11 \)[/tex]
The piecewise function is defined as:
[tex]\[ f(x) = \begin{cases} 3x + 4 & \text{if } x < 0 \\ x + 7 & \text{if } x \geq 0 \end{cases} \][/tex]
Let's evaluate the function at each given value:
### (a) [tex]\( f(-2) \)[/tex]
For [tex]\( x = -2 \)[/tex]:
- Since [tex]\( -2 < 0 \)[/tex], we use the first piece of the function: [tex]\( f(x) = 3x + 4 \)[/tex].
- Substituting [tex]\( x = -2 \)[/tex] into this piece:
[tex]\[ f(-2) = 3(-2) + 4 = -6 + 4 = -2 \][/tex]
Thus, [tex]\( f(-2) = -2 \)[/tex].
### (b) [tex]\( f(0) \)[/tex]
For [tex]\( x = 0 \)[/tex]:
- Since [tex]\( 0 \geq 0 \)[/tex], we use the second piece of the function: [tex]\( f(x) = x + 7 \)[/tex].
- Substituting [tex]\( x = 0 \)[/tex] into this piece:
[tex]\[ f(0) = 0 + 7 = 7 \][/tex]
Thus, [tex]\( f(0) = 7 \)[/tex].
### (c) [tex]\( f(4) \)[/tex]
For [tex]\( x = 4 \)[/tex]:
- Since [tex]\( 4 \geq 0 \)[/tex], we use the second piece of the function: [tex]\( f(x) = x + 7 \)[/tex].
- Substituting [tex]\( x = 4 \)[/tex] into this piece:
[tex]\[ f(4) = 4 + 7 = 11 \][/tex]
Thus, [tex]\( f(4) = 11 \)[/tex].
To summarize:
- (a) [tex]\( f(-2) = -2 \)[/tex]
- (b) [tex]\( f(0) = 7 \)[/tex]
- (c) [tex]\( f(4) = 11 \)[/tex]
Therefore, the values of the function at the given points are:
- [tex]\( f(-2) = -2 \)[/tex]
- [tex]\( f(0) = 7 \)[/tex]
- [tex]\( f(4) = 11 \)[/tex]
We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Westonci.ca is your go-to source for reliable answers. Return soon for more expert insights.